1987
DOI: 10.1001/archotol.1987.01860030075012
|View full text |Cite
|
Sign up to set email alerts
|

Far-Advanced Otosclerosis: Cochlear Implantation vs Stapedectomy

Abstract: \s=b\In 1981, our group, as part of a Food and Drug Administration investigator team directed by William House, performed Illinois' first cochlear implantation. We have since performed cochlear implantations in ten other persons. Since May 1980, approximately 35 severely to profoundly deaf persons per year have been referred to our clinic for evaluation. A small number of these patients had far-advanced otosclerosis. In these cases, exploratory tympanotomy and stapedectomy followed by rehabilitation with a hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…The results after stapedotomy were variable: 46% to 100% of the patients achieved an improvement in hearing 5, 6, 14–25. The SD scores after stapedotomy were between 38% and 75% 5, 6, 17, 18, 21–24. Shea et al25 divided their patients into different cohorts based on the air‐ and bone‐conduction thresholds.…”
Section: Resultsmentioning
confidence: 99%
“…The results after stapedotomy were variable: 46% to 100% of the patients achieved an improvement in hearing 5, 6, 14–25. The SD scores after stapedotomy were between 38% and 75% 5, 6, 17, 18, 21–24. Shea et al25 divided their patients into different cohorts based on the air‐ and bone‐conduction thresholds.…”
Section: Resultsmentioning
confidence: 99%
“…Binaural speech recognition measurement demonstrates the benefit of binaural processing as the binaural speech recognition increased to 88% (F 3 ). and better performance in the presence of background noise (20).…”
Section: Speech Recognition Outcomes After Stapedotomymentioning
confidence: 99%
“…The standard criterion for measuring the success of stapedotomy, closure of the air-bone gap to 10 dB or less, is not relevant in patients with FAO because bone conduction levels are often immeasurable even postoperatively (18,20,21). Likewise, the commonly used Belfast Rule of Thumb (stating that patients are likely to benefit from stapedotomy if the hearing threshold in the operated ear is brought to 30 dB HL or better or within 15 dB of contralateral ear) does not seem to be applicable for estimating the effect of stapedotomy in patients with FAO (22).…”
Section: Clinical Recommendationmentioning
confidence: 99%
“…Schuknecht and Barber (1985) showed no correlation between bone-conduction thresholds and size of the lesion, activity of the lesion, involvement of endosteum or presence of a round window lesion. On the other hand, Wiet et al (1987) reported moderate diffuse loss of hair cells and loss of cochlear neurons in the basal turn. Myers and Myers (1968) found atrophy of the spiral ligament with basilar membrane rupture.…”
Section: Discussionmentioning
confidence: 96%
“…The patients must be aware not only of the risks of the procedure, but also of the relatively limited goals. Normal hearing is not expected and the patient should be cautioned that amplification via a hearing aid will probably be needed after surgery to receive the optimum potential benefit (Wiet et al, 1987). Sheehy (1978) found that in FAO the success rate was higher in those patients who had been wearing a hearing aid pre-operatively, ie.…”
Section: Discussionmentioning
confidence: 99%